Evaluation of the effects of sodium valproate on plasma homocysteine, folate and vitamin B12 levels in epileptic patients - A. Aman-Mohammady; D. Qujeq; P. Saadat; K. Hajian-Tilaki (Эпилепсия и пароксизмальные состояния, 2024)
Objective: to investigate the effects of sodium valproate on plasma concentrations of homocysteine, folate and vitamin B12 levels in epileptic patients with long-standing tonic-clonic seizures compared to newly diagnosed epileptic patients and healthy controls.Material and methods. The study included 90 participants (mean age 36.30±12.83 years, the majority (58.89%) were males) divided into three groups: 30 non-epileptic people (control Group 1), 30 newly diagnosed epileptic patients (Group 2), and 30 patients with long-term tonic-clonic seizures epilepsy (Group 3). In Group 3, patients received sodium valproate therapy. All subjects underwent clinical and neurological examinations. Differences in plasma levels of homocysteine, folic acid and vitamin B12 in three groups were investigated after 6 months of follow-up.Results. Homocysteine level in Groups 2 and 3 was increased; for Group 2 it was significantly higher than for Groups 3 and 1 (p=0.001). Plasma folate level in Groups 2 and 3 was decreased; for Group 3 it was significantly higher than for Group 2 and lower than for Group 1 (p=0.001). Vitamin B12 level in Groups 2 and 3 was decreased, but the difference was not significant (p=0.090). In Groups 1 and 2, a significant correlation was observed between the indicators.Conclusion. Sodium valproate аdministration might disrupt the homeostatic level of homocysteine, folate and vitamin B12 and cause irregularity of their plasma contents in epileptic patients with long-standing tonic-clonic seizures.